Early Initiation of Anticoagulation with Direct Oral Anticoagulants in Patients after Transient Ischemic Attack or Ischemic Stroke - Macha, Kosmas; Volbers, Bastian; Bobinger, Tobias; Kurka, Natalia; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2016)
Direct oral anticoagulants (DOACs) are increasingly used for secondary prevention of cardioembolic stroke. While DOACs are associated with a long-term reduced risk of intracranial hemorrhage compared to vitamin K antagonists, pivotal trials avoided the very early period after stroke and few data exist on early initiation of DOAC therapy post stroke.We retrospectively analyzed data from our prospective database of all consecutive transient ischemic attack (TIA) or ischemic stroke patients with atrial fibrillation treated with DOACs during hospital stay. As per our institutional treatment algorithm for patients with cardioembolic ischemia DOACs are started immediately in TIA and minor stroke (group 1), within days 3-5 in patients with infarcts affecting one third or less of the middle cerebral artery, the anterior cerebral artery, or the posterior cerebral artery territories (group 2) as well as in infratentorial stroke (group 3) and after 1-2 weeks in patients with large infarcts (> 1/3 MCA territory, group 4). We investigated baseline characteristics, time to initiation of DOAC therapy after symptom onset, and hemorrhagic complications.In 243 included patients, administration of DOAC was initiated 40.5 hours (interquartile range [IQR] 23.0-65.5) after stroke onset in group 1 (n = 41) and after 76.7 hours (IQR 48.0-134.0), 108.4 hours (IQR 67.3-176.4), and 161.8 hours (IQR 153.9-593.8) in groups 2-4 (n = 170, 28, and 4), respectively. Two cases of asymptomatic intracranial hemorrhage (.8%) and 1 case of symptomatic intracranial hemorrhage (.4%) were observed, both in group 2.No severe safety issues were observed in early initiation of DOACs for secondary prevention after acute stroke in our in-patient cohort.
EVALuna2:22461